2013
DOI: 10.1007/s10995-013-1402-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Associated Cardiovascular Risk Factors in Guatemalan School Children

Abstract: Objectives Guatemala is experiencing a nutritional and lifestyle transition. While chronic malnutrition is prevalent, overweight, obesity and chronic diseases have increased substantially in the country. This study was conducted to investigate the prevalence of metabolic syndrome and the associated cardiovascular risk factors in the pre-adolescent Guatemalan population. Methods A cross-sectional study was conducted among 302 Guatemalan children (8–13 years old) attending public and private schools in the Mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
15
0
4
Order By: Relevance
“…Los datos reportados son el resultado del análisis de 23 artículos que cumplieron con los criterios de inclusión, y que corresponden a 12 países de América: Argentina [15][16][17][18] , Brasil 19 , Canadá [20][21] , Chile [22][23][24] , Colombia [25][26][27] , Ecuador 28 , Estados Unidos de América (EUA) 29 , Guatemala 30 , México [31][32][33][34] , Paraguay 35 , Perú 36 y Venezuela 37 . Del total de estudios analizados, solamente 21 trabajos mostraron prevalencias generales de obesidad abdominal, 18 de ellos tuvieron prevalencias de hiperglucemia, otros 18 indicaron las prevalencias de hipertrigliceridemia, 19 las prevalencias de hipoalfalipoproteinemia (HDL-C bajo), 20 más midieron prevalencias de hipertensión arterial, y 18 analizaron prevalencias del SM.…”
Section: Resultsunclassified
“…Los datos reportados son el resultado del análisis de 23 artículos que cumplieron con los criterios de inclusión, y que corresponden a 12 países de América: Argentina [15][16][17][18] , Brasil 19 , Canadá [20][21] , Chile [22][23][24] , Colombia [25][26][27] , Ecuador 28 , Estados Unidos de América (EUA) 29 , Guatemala 30 , México [31][32][33][34] , Paraguay 35 , Perú 36 y Venezuela 37 . Del total de estudios analizados, solamente 21 trabajos mostraron prevalencias generales de obesidad abdominal, 18 de ellos tuvieron prevalencias de hiperglucemia, otros 18 indicaron las prevalencias de hipertrigliceridemia, 19 las prevalencias de hipoalfalipoproteinemia (HDL-C bajo), 20 más midieron prevalencias de hipertensión arterial, y 18 analizaron prevalencias del SM.…”
Section: Resultsunclassified
“…Among schoolchildren and adolescents from Mérida (Mexico) aged 9-18 years, the prevalence of MetS was 2.2% and 1.8% according to the percentiles obtained by Cook-Merida and Cook-USA, respectively [29]. In Guatemalan children (aged 8-13 years) from public and private schools, the MetS prevalence was 2.0% with no significant difference between boys and girls [30]. When compared to other Brazilian studies, the present results are well below those found in the literature, as in the study of 12-to 19-year-old schoolchildren from public schools in Niteroi, State of Rio de Janeiro, where the prevalence of MetS was 13.8% and 2.4% for boys and girls, respectively [15].…”
Section: Discussionmentioning
confidence: 87%
“…Em um estudo desenvolvido na Guatemala, com 302 crianças/adolescentes, constatou-se a prevalência de SM de 2,0%, entretanto, em aproximadamente 54% dos participantes, verificou-se pelo menos um componente da SM (25) . Já em um estudo desenvolvido na Coreia, com 1554 adolescentes de 10 a 19 anos, constatou-se a prevalência de SM de 2,3% na amostra total, de 2,8% em adolescentes com sobrepeso e de 23,7% em adolescentes obesos (26) .…”
Section: Discussionunclassified